Avaliação do efeito da adição do pellet, umidade e cal, nos parâmetros de uma sinterização piloto - Fernando Gustavo Correa de Melo (2019)
The pellet feed addition in conventional sintering has become a common practice due to the increased sinter feed silica content, requiring adjustments to the sintering process routes. With the acquisition of the intensive mixer, CSN increased the share of pellet feed in the mix to sinter in its industrial process. In this context, the effect of increasing the participation of the pellet feed in the mixture to be sintered from 15% to 20% in the pilot sintering process was evaluated using the intensive mixer. The results indicated variation in productivity, sinter yield and sinter mechanical properties as presented in the present study.